Revitalisasi Dinding Melalui Pembuatan Mural dengan Narasi Sejarah Jamblang, Cirebon: Wall Revitalization Through Making Murals with Jamblang History Narrative, Cirebon - Miky Endro Santoso; Elliati Djakaria; Tessa Eka Darmayanti; Krismanto Kusbiantoro; Cindrawaty Lesmana; Irfan Nurrachman; Ferlina Sugata; Leonardo Leonardo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Jamblang Chinatown, Cirebon was once known as a trading city during the Dutch colonial period, as a place for buying and selling and stopping by traders from various regions through the river that flows nearby. The river is a means of transportation that brings ships from the interior of Cirebon to the Java Sea, and vice versa. However, the current situation is reversed because Jamblang is like a